MHD Study of Extreme Space Weather Conditions for Exoplanets With Earth‐Like Magnetospheres: On Habitability Conditions and Radio‐Emission - J. Varela; A. S. Brun; P. Zarka; A. Strugarek; F. Pantellini; V. Réville (Space Weather)
Abstract The present study aims at characterizing the habitability conditions of exoplanets with an Earth‐like magnetosphere inside the habitable zone of M and F stars, caused by the direct deposition of the stellar wind on the exoplanet surface. Also, the radio emission generated by exoplanets with a Earth‐like magnetosphere is calculated for different space weather conditions. The study is based on a set of MHD simulations performed by the code PLUTO. Exoplanets hosted by M stars at 0.2 au are protected from the stellar wind during regular and coronal mass ejection (CME)‐like space weather conditions if the star rotation period is slower than 3 days. Exoplanets hosted by a F stars at ≥2.5 au are protected during regular space weather conditions, but a stronger magnetic field compared to the Earth is mandatory if the exoplanet is close to the inner edge of the star habitable zone (2.5 au) during CMEs. The range of radio emission values calculated in the simulations are consistent with the scaling proposed by Zarka (2018, https://doi.org/10.1007/978-3-319-55333-7_22) during regular and common CME‐like space weather conditions. If the radio telescopes measure a relative low radio emission signal with small variability from an exoplanet, that may indicate favorable exoplanet habitability conditions. The radio emission power calculated for exoplanets with an Earth‐like magnetosphere is in the range of 3 × 107 to 2 × 1010 W for SW dynamic pressures between 1.5 and 100 nPa and interplanetary magnetic field intensities between 50 and 250 nT, and is below the sensitivity threshold of present radio telescopes at parsec distances.